2020
DOI: 10.32854/agrop.vi.1608
|View full text |Cite
|
Sign up to set email alerts
|

Obtención de celulosa a partir de residuos de piña (Ananas Comosus L. Merril)

Abstract: Objetivo: Este trabajo explora la obtención de celulosa de alta calidad a partir de residuos de piña.   Diseño/metodología/aproximación: Se utilizaron coronas de piña para la obtención de la celulosa utilizando el tratamiento de pre-hidrólisis ácida al 0.5% con ácido sulfúrico combinado con el método de pulpeo Sosa-Antraquinona (SQ) y blanqueo libre de cloro elemental (ECF).  La celulosa obtenida fue caracterizada por las técnicas TAPPI de Espectroscopia Infrarroja por Transformada de Fourier (FTIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…Other elements present in triticale and barley straw can be seen in Figure 4, such as: N, Si, Al, Na, Cu, Mg, K, Ca, Fe, Cl, P. The content of these elements was low, if one takes into account the amount of ashes. Similar results were reported for plant materials [27,36,50,51]. Other minor elements, such as S, P, Na and Al, were also detected, according to the analytical technique used [52][53][54][55][56].…”
Section: Characterization Of the Straws By Energy Dispersive X-ray De...supporting
confidence: 85%
“…Other elements present in triticale and barley straw can be seen in Figure 4, such as: N, Si, Al, Na, Cu, Mg, K, Ca, Fe, Cl, P. The content of these elements was low, if one takes into account the amount of ashes. Similar results were reported for plant materials [27,36,50,51]. Other minor elements, such as S, P, Na and Al, were also detected, according to the analytical technique used [52][53][54][55][56].…”
Section: Characterization Of the Straws By Energy Dispersive X-ray De...supporting
confidence: 85%
“…Table 1 shows the cellulose fiber yield (%), which is lower compared to: banana pseudo-stem residues with yield of 66% (Bolio et al, 2011), sugarcane bagasse with 48% (López-Martínez et al, 2016), and the one found in platanillo (Heliconia latispatha) with 46% of cellulose obtained (García Fajardo, 2015). On the other hand, the yield obtained from the palm bagasse is higher than 29.3% obtained in residues of pineapple crown (Presenda et al, 2020) and the 34% of final cellulose yield from sugarcane hay by Bolio et al (2017).…”
Section: Cellulose Extractionmentioning
confidence: 78%